A method for improving the cycle performance of aqueous zinc-ion batteries
By applying pulse current to the aqueous zinc ion battery, the deposition morphology of zinc on the negative electrode side is regulated, and the battery inactivation problem caused by zinc dendrites is solved, which significantly improves the cycling performance and service life of the battery.
Patent Information
- Application Number
- CN202311048896.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-08-18
AI Technical Summary
During the circulation process, the aqueous zinc ion battery forms zinc dendrites due to uneven deposition of zinc on the negative electrode surface, resulting in short circuit or peeling and inactivation of the piercing membrane, reducing the battery's Coulomb efficiency and service life.
By applying pulse current to the aqueous zinc ion battery, the deposition morphology of zinc on the negative electrode side is regulated and the uniformity of zinc deposition is improved.
It effectively extends the battery life, improves the circulation performance of aqueous zinc ion batteries, and prevents the formation of zinc dendrites and related inactivation problems.
Smart Images

Figure CN117059923B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for improving the cycle performance of an aqueous zinc ion battery, and belongs to the technical field of zinc ion batteries. Background Art
[0002] With the continuous development of society, highly safe, stable, low-cost and environmentally friendly electrochemical energy storage systems have attracted more and more attention. Aqueous zinc-ion batteries have high power density and energy density, and use aqueous salts as electrolytes. They have low requirements for the production environment, are easy to recycle, and are green and safe, making them a popular choice for the development of energy storage equipment.
[0003] In the process of zinc ion storage, commercial zinc is usually used as the negative electrode material, which has high theoretical capacity, low potential, high abundance, low toxicity and high safety, and is considered to be an ideal negative electrode material for aqueous batteries. Zinc ions are embedded / extracted in the tunnel of the positive electrode material, and dissolved / deposited at the zinc negative electrode at the same time, during which electrons are transferred, forming an aqueous zinc ion battery; however, during the continuous dissolution / deposition cycle of the aqueous zinc ion battery, due to the uneven deposition of zinc metal on the negative electrode surface, zinc dendrites will be formed and accompanied by side reactions, and the continuous growth of zinc dendrites will cause puncture of the diaphragm short circuit or peeling and inactivation, reducing the coulomb efficiency of the battery, causing the battery capacity to decay rapidly, greatly reducing the battery life, and severely limiting the further development of aqueous zinc ion batteries. Summary of the invention
[0004] In order to overcome the defects of the prior art, the object of the present invention is to provide a method for improving the cycle performance of an aqueous zinc ion battery. The method applies a pulse current to the aqueous zinc ion battery, effectively regulates the deposition morphology of zinc on the negative electrode side during the cycle of the zinc ion battery, improves the uniformity of zinc deposition, thereby effectively extending the life of the battery and improving the cycle performance of the aqueous zinc ion battery.
[0005] The objectives of the present invention are achieved through the following technical solutions.
[0006] A method for improving the cycle performance of an aqueous zinc ion battery, the method comprising applying a pulse current to the aqueous zinc ion battery; the aqueous zinc ion battery is an aqueous zinc ion battery conventionally used in the existing zinc ion battery field and has not been used; the aqueous zinc ion battery is generally composed of a positive electrode, a negative electrode, a diaphragm and an electrolyte; wherein the positive electrode and the negative electrode are respectively independent zinc-containing metal materials; the electrolyte is a zinc salt aqueous solution; the diaphragm is a diaphragm material conventionally used in the aqueous zinc ion battery field in the prior art;
[0007] The aqueous zinc ion battery is powered on and off once as one cycle, and a plurality of cycles are repeated to form a pulse current; in each cycle, the power-on time is 1 to 10 seconds, the power-off time is 0.5 to 50 seconds, and the power-on-power-off time ratio is 1:0.5 to 1:5; the current density of the pulse current is 0.5 to 3 mA / cm 2 The power-on-power-off cycle is repeated until the negative electrode deposition capacity of the aqueous zinc ion battery is 0.5-3 mAh / cm 2 .
[0008] Preferably, in each cycle, the power-on time is 1 to 10 seconds and the power-off time is 3 to 50 seconds; the power-on-power-off cycle is repeated until the overpotential of the aqueous zinc ion battery reaches above 0.1V.
[0009] Preferably, the positive electrode and the negative electrode of the aqueous zinc ion battery are respectively independent zinc foils or zinc alloy foils.
[0010] Preferably, the separator of the aqueous zinc ion battery is a glass fiber membrane, a PP film (polypropylene film) or a PE film (polyethylene film).
[0011] Preferably, the electrolyte of the aqueous zinc ion battery is an aqueous solution of zinc sulfate, an aqueous solution of zinc tetrafluoroborate or an aqueous solution of zinc trifluoromethanesulfonate; in the electrolyte, the concentration of zinc ions is 0.2 to 5 mol / L.
[0012] Further preferably, the positive electrode and the negative electrode of the aqueous zinc ion battery are respectively independent zinc foils; the diaphragm of the aqueous zinc ion battery is a glass fiber membrane; the electrolyte of the aqueous zinc ion battery is an aqueous zinc sulfate solution, and the concentration of zinc ions in the electrolyte is 2 mol / L.
[0013] Beneficial Effects
[0014] (1) The present invention provides a method for improving the cycle performance of an aqueous zinc ion battery. The method applies a pulse current to a brand new aqueous zinc ion battery that has not been operated, thereby effectively regulating the deposition morphology of zinc on the negative electrode side during the operation of the aqueous zinc ion battery and improving the uniformity of zinc deposition. This overcomes the problem in the prior art that zinc is unevenly deposited on the negative electrode side surface during the operation of the aqueous zinc ion battery to form zinc dendrites, which ultimately pierces the diaphragm to cause a short circuit or peels off and inactivates, thereby reducing the performance of the battery. The overall cycle performance of the aqueous zinc ion battery is significantly improved.
[0015] (2) The present invention provides a method for improving the cycle performance of an aqueous zinc ion battery. The method limits the power-on time to 1 to 10 seconds, the power-off time to 0.5 to 50 seconds, and the power-on-power-off time ratio to 1:0.5 to 1:5 in each power-on-power-off cycle of a pulse current; when the power-on-power-off time ratio is too low, the power-on time is too short and the zinc deposition morphology cannot be effectively regulated; when the power-on-power-off time ratio is too high, the power-on time is too long, which increases the overpotential of the aqueous zinc ion battery. The power-on time, the power-off time and the on-off-power-off time ratio can effectively regulate the zinc deposition morphology and uniformity, thereby improving the cycle performance of the aqueous zinc ion battery.
[0016] (3) The present invention provides a method for improving the cycle performance of an aqueous zinc ion battery. The method has simple steps and is easy to operate. It can effectively extend the life of the aqueous zinc ion battery, improve the cycle performance and safety of the aqueous zinc ion battery, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a cycle performance diagram of the Zn / Zn battery assembled in Example 1.
[0018] Figure 2 This is a scanning electron microscope (SEM) image of the negative electrode of the Zn / Zn battery assembled in Example 2 after the battery cycle is completed.
[0019] Figure 3 This is a cycle performance diagram of the Zn / Zn battery assembled in Comparative Example 1.
[0020] Figure 4 This is a scanning electron microscope (SEM) image of the negative electrode of the Zn / Zn battery assembled in Example 2 after the cycle is completed. DETAILED DESCRIPTION
[0021] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments. The methods described are all conventional methods unless otherwise specified, and the raw materials described can be obtained from public commercial channels unless otherwise specified.
[0022] In the following comparative examples and embodiments:
[0023] (1) Micromorphology characterization: Observation was performed using a field emission scanning electron microscope (FEIQuanta 600) with an accelerating voltage of 25 kV;
[0024] (2) Cyclic performance test: The assembled CR 2032 type Zn / Zn pair battery was subjected to a cyclic performance test using the Land system, and the test data was recorded.
[0025] Example 1
[0026] A method for improving the cycle performance of an aqueous zinc ion battery, the method comprising applying a pulse current to the aqueous zinc ion battery;
[0027] The aqueous zinc ion battery is a CR 2032 type Zn / Zn pair battery assembled by a positive electrode, a negative electrode, a separator and an electrolyte; wherein the positive electrode and the negative electrode are both 1 cm 2 The pure zinc foil; the electrolyte is a zinc sulfate aqueous solution with a zinc ion concentration of 2 mol / L; the diaphragm is a glass fiber membrane;
[0028] The aqueous zinc ion battery is powered on and off once to form a cycle, and several cycles are repeated to form a pulse current; in each cycle of the pulse current, the power-on time is 10s, the power-off time is 30s, the power-on-power-off time ratio is 1:3, and the current density of the pulse current is 1mA / cm 2 ; Under the above conditions, the CR 2032 Zn / Zn battery was subjected to a cycle performance test until the negative electrode deposition capacity was 1 mAh / cm 2 , the cycle performance test results are as follows Figure 1 As shown, after 140 hours of cycling, the overpotential of the CR2032 Zn / Zn battery tested under pulse current conditions is still relatively stable at 0.045V. The overpotential is less than 0.1V, indicating that the aqueous zinc ion battery is not damaged and still has a tendency to continue cycling, indicating that the method described in this embodiment can effectively improve the cycling performance of the aqueous zinc ion battery.
[0029] The surface morphology of the negative electrode after the cycle was completed was observed using a field emission scanning electron microscope. It can be seen that the deposition morphology of Zn on the negative electrode side is uniform and flat, and there is no obvious large cluster-like zinc deposition morphology. This shows that the method described in this embodiment can effectively inhibit the dendrite phenomenon of the negative electrode during the cycle of the aqueous zinc ion battery, regulate the deposition morphology of zinc on the negative electrode side, and improve the uniformity of zinc deposition.
[0030] Example 2
[0031] Example 2 is based on Example 1, and the negative electrode deposition capacity is increased from "1 mAh / cm 2 " is replaced by "3mAh / cm 2 ", other conditions remain unchanged; under the above conditions, the cycle performance test of the aqueous zinc ion battery described in Example 2 is carried out. After 138h of cycling, the overpotential of the CR 2032 Zn / Zn pair battery tested under the condition of applying pulse current is still relatively stable and maintained at 0.05V. The overpotential is less than 0.1V, which indicates that the aqueous zinc ion battery is not damaged and still has a trend of continuing to cycle, indicating that the method described in this embodiment can effectively improve the cycle performance of the aqueous zinc ion battery.
[0032] Field emission scanning electron microscopy was used to observe the surface morphology of the negative electrode after the cycle. Figure 2 As shown, the deposition morphology of Zn on the negative electrode side is uniform and flat, and there is no obvious large cluster-like zinc deposition morphology, which shows that the method described in this embodiment can effectively inhibit the dendrite phenomenon of the negative electrode during the cycle of the aqueous zinc ion battery, regulate the deposition morphology of zinc on the negative electrode side, and improve the uniformity of zinc deposition.
[0033] Example 3
[0034] Example 3 is based on Example 1, except that in each cycle of the pulse current, "the power-on time is 10s, the power-off time is 30s, and the power-on-power-off time ratio is 1:3" is replaced by "the power-on time is 10s, the power-off time is 5s, and the power-on-power-off time ratio is 1:0.5", and other conditions remain unchanged.
[0035] Under the above conditions, the CR 2032 Zn / Zn pair battery was subjected to a long cycle performance test until the negative electrode deposition capacity reached 1 mAh / cm 2 The cycle performance test results show that the overpotential of the CR 2032 Zn / Zn battery tested under pulse current conditions is still relatively stable at 0.058V after 115h of cycling. The overpotential is less than 0.1V, indicating that the aqueous zinc ion battery is not damaged and still has a tendency to continue cycling, indicating that the method described in this embodiment can effectively improve the cycle performance of the aqueous zinc ion battery.
[0036] The surface morphology of the negative electrode after the cycle was completed was observed using a field emission scanning electron microscope. It can be seen that the deposition morphology of Zn on the negative electrode side is uniform and flat, and there is no obvious large cluster-like zinc deposition morphology. This shows that the method described in this embodiment can effectively inhibit the dendrite phenomenon of the negative electrode during the cycle of the aqueous zinc ion battery, regulate the deposition morphology of zinc on the negative electrode side, and improve the uniformity of zinc deposition.
[0037] Example 4
[0038] Example 4 is based on Example 3, and the negative electrode deposition capacity is increased from "1 mAh / cm 2 " is replaced by "3mAh / cm 2 ", other conditions remain unchanged; under the above conditions, the cycle performance of the aqueous zinc ion battery is tested. After 112h of cycling, the overpotential of the CR 2032 Zn / Zn pair battery tested under the condition of applying pulse current is still relatively stable at 0.06V. The overpotential is less than 0.1V, indicating that the aqueous zinc ion battery is not damaged and still has a trend of continuing to cycle, indicating that the method described in this embodiment can effectively improve the cycle performance of the aqueous zinc ion battery.
[0039] The surface morphology of the negative electrode after the cycle was completed was observed using a field emission scanning electron microscope. The test results showed that the deposition morphology of Zn on the negative electrode side was uniform and flat, and there was no obvious large cluster-like zinc deposition morphology. This shows that the method described in this embodiment can effectively inhibit the dendrite phenomenon of the negative electrode during the cycle of the aqueous zinc ion battery, regulate the deposition morphology of zinc on the negative electrode side, and improve the uniformity of zinc deposition.
[0040] Example 5
[0041] Example 5 Based on Example 1, "power-on time is 10s, power-off time is 30s, and power-on-power-off time ratio is 1:3" in each cycle of the pulse current is replaced by "power-on time is 10s, power-off time is 50s, and power-on-power-off time ratio is 1:5", and other conditions remain unchanged; under the above conditions, the CR 2032 Zn / Zn pair battery is subjected to a cycle performance test until the negative electrode deposition capacity is 1 mAh / cm 2 The cycle performance test results show that the overpotential of the CR 2032 Zn / Zn battery tested under pulse current conditions remains relatively stable at 0.056V after 125h of cycling. The overpotential is less than 0.1V, indicating that the aqueous zinc ion battery is not damaged and still has a tendency to continue cycling, indicating that the method described in this embodiment can effectively improve the cycle performance of the aqueous zinc ion battery.
[0042] The surface morphology of the negative electrode after the cycle was completed was observed using a field emission scanning electron microscope. It can be seen that the deposition morphology of Zn on the negative electrode side is uniform and flat, and there is no obvious large cluster-like zinc deposition morphology. This shows that the method described in this embodiment can effectively inhibit the dendrite phenomenon of the negative electrode during the cycle of the aqueous zinc ion battery, regulate the deposition morphology of zinc on the negative electrode side, and improve the uniformity of zinc deposition.
[0043] Example 6
[0044] Example 6 is based on Example 5, and the negative electrode deposition capacity is increased from "1 mAh / cm 2 " is replaced by "3mAh / cm 2 ", other conditions remain unchanged; under the above conditions, the cycle performance of the aqueous zinc ion battery is tested. After 122h of cycling, the overpotential of the CR 2032 Zn / Zn pair battery tested under the condition of applying a pulse current is still relatively stable and maintained at 0.058V. The overpotential is less than 0.1V, indicating that the aqueous zinc ion battery is not damaged and still has a tendency to continue cycling, indicating that the method described in this embodiment can effectively improve the cycle performance of the aqueous zinc ion battery.
[0045] The surface morphology of the negative electrode after the cycle was completed was observed using a field emission scanning electron microscope. The test results showed that the deposition morphology of Zn on the negative electrode side was uniform and flat, and there was no obvious large cluster-like zinc deposition morphology. This shows that the method described in this embodiment can effectively inhibit the dendrite phenomenon of the negative electrode during the cycle of the aqueous zinc ion battery, regulate the deposition morphology of zinc on the negative electrode side, and improve the uniformity of zinc deposition.
[0046] Example 7
[0047] Example 7 Based on Example 1, the "power-on time is 10s, the power-off time is 30s, and the power-on-power-off time ratio is 1:3" in each cycle of the pulse current is replaced by "power-on time is 1s, the power-off time is 3s, and the power-on-power-off time ratio is 1:3", and other conditions remain unchanged; under the above conditions, the CR 2032 Zn / Zn pair battery is subjected to a cycle performance test until the negative electrode deposition capacity is 1 mAh / cm 2 The cycle performance test results show that the overpotential of the CR 2032 Zn / Zn battery tested under pulse current conditions is still relatively stable at 0.057V after 118h of cycling. The overpotential is less than 0.1V, indicating that the aqueous zinc ion battery is not damaged and still has a tendency to continue cycling, indicating that the method described in this embodiment can effectively improve the cycle performance of the aqueous zinc ion battery.
[0048] The surface morphology of the negative electrode after the cycle was completed was observed using a field emission scanning electron microscope. It can be seen that the deposition morphology of Zn on the negative electrode side is uniform and flat, and there is no obvious large cluster-like zinc deposition morphology. This shows that the method described in this embodiment can effectively inhibit the dendrite phenomenon of the negative electrode during the cycle of the aqueous zinc ion battery, regulate the deposition morphology of zinc on the negative electrode side, and improve the uniformity of zinc deposition.
[0049] Example 8
[0050] Example 8 is based on Example 7, and the negative electrode deposition capacity is increased from "1 mAh / cm 2 " is replaced by "3mAh / cm 2 ", other conditions remain unchanged; under the above conditions, the cycle performance of the aqueous zinc ion battery is tested. After 117h of cycling, the overpotential of the CR 2032 Zn / Zn pair battery tested under the condition of applying pulse current is still relatively stable at 0.059V. The overpotential is less than 0.1V, indicating that the aqueous zinc ion battery is not damaged and still has a trend of continuing to cycle, indicating that the method described in this embodiment can effectively improve the cycle performance of the aqueous zinc ion battery.
[0051] The surface morphology of the negative electrode after the cycle was completed was observed using a field emission scanning electron microscope. The test results showed that the deposition morphology of Zn on the negative electrode side was uniform and flat, and there was no obvious large cluster-like zinc deposition morphology. This shows that the method described in this embodiment can effectively inhibit the dendrite phenomenon of the negative electrode during the cycle of the aqueous zinc ion battery, regulate the deposition morphology of zinc on the negative electrode side, and improve the uniformity of zinc deposition.
[0052] Comparative Example 1
[0053] Comparative Example 1 is based on Example 1, except that "pulse current" is replaced by "direct current", and other conditions remain unchanged; under the above conditions, the cycle performance of the aqueous zinc ion battery is tested, and the results are as follows Figure 3 As shown, the overpotential of the CR 2032 Zn / Zn battery tested under DC current conditions increased sharply to 0.1 V after 74 hours of cycling, and the aqueous zinc ion battery was damaged.
[0054] Field emission scanning electron microscopy was used to observe the surface morphology of the negative electrode after the cycle. The test results showed that Zn had obvious large clusters of zinc deposition morphology on the negative electrode side, and dendrites occurred at the negative electrode during the cycle of aqueous zinc-ion batteries.
[0055] Comparative Example 2
[0056] Comparative Example 2 is based on Comparative Example 1, and the deposition capacity of the negative electrode is increased from "1 mAh / cm 2 " is replaced by "3mAh / cm 2 ", other conditions remain unchanged; under the above conditions, the cycle performance of the aqueous zinc ion battery is tested. The results show that after 72h of cycling, the overpotential of the CR 2032 Zn / Zn pair battery tested under the condition of applying direct current increases sharply to 0.102V, and the aqueous zinc ion battery is damaged.
[0057] Field emission scanning electron microscopy was used to observe the surface morphology of the negative electrode after the cycle. The test results are as follows: Figure 4 As shown, Zn has obvious large cluster-like zinc deposition morphology on the negative electrode side, and the dendrite phenomenon of the negative electrode during the cycling of aqueous zinc-ion batteries.
[0058] Comparative Example 3
[0059] Comparative Example 3 is based only on Example 1, except that "the power-on time is 10s, the power-off time is 30s, and the power-on-power-off time ratio is 1:3" is replaced by "the power-on time is 10s, the power-off time is 70s, and the power-on-power-off time ratio is 1:7", and other conditions remain unchanged; under the above conditions, the cycle performance of the aqueous zinc ion battery is tested. The test results show that the overpotential of the CR 2032 Zn / Zn pair battery tested under the condition of applying a pulse current increases sharply to 0.108V after 100h of circulation, and the aqueous zinc ion battery is damaged.
[0060] Field emission scanning electron microscopy was used to observe the surface morphology of the negative electrode after the cycle. The test results showed that Zn had obvious large clusters of zinc deposition morphology on the negative electrode side, and dendrites occurred at the negative electrode during the cycle of aqueous zinc-ion batteries.
[0061] Comparative Example 4
[0062] Comparative Example 4 is based on Comparative Example 3, and the deposition capacity of the negative electrode is increased from "1 mAh / cm 2 " is replaced by "3mAh / cm 2 ", other conditions remain unchanged; under the above conditions, the cycle performance of the aqueous zinc ion battery is tested. The results show that after 99h of cycling, the overpotential of the CR 2032 Zn / Zn pair battery tested under the condition of applying pulse current increases sharply to 0.112V, and the aqueous zinc ion battery is damaged.
[0063] Field emission scanning electron microscopy was used to observe the surface morphology of the negative electrode after the cycle. The test results showed that Zn had obvious large clusters of zinc deposition morphology on the negative electrode side, and dendrites occurred at the negative electrode during the cycle of aqueous zinc-ion batteries.
[0064] Comparative Example 5
[0065] Comparative Example 5 is based only on Example 1, except that "the power-on time is 10 s, the power-off time is 30 s, and the power-on-power-off time ratio is 1:3" is replaced by "the power-on time is 0.5 s, the power-off time is 1.5 s, and the power-on-power-off time ratio is 1:3", and other conditions remain unchanged; under the above conditions, the cycle performance of the aqueous zinc ion battery is tested. The test results show that the overpotential of the CR 2032 Zn / Zn pair battery tested under the condition of applying a pulse current increases sharply to 0.115 V after 80 hours of circulation, and the aqueous zinc ion battery is damaged.
[0066] Field emission scanning electron microscopy was used to observe the surface morphology of the negative electrode after the cycle. The test results showed that Zn had obvious large clusters of zinc deposition morphology on the negative electrode side, and dendrites occurred at the negative electrode during the cycle of aqueous zinc-ion batteries.
[0067] Comparative Example 6
[0068] Comparative Example 6 is based on Comparative Example 5, and the deposition capacity of the negative electrode is increased from "1 mAh / cm 2 " is replaced by "3mAh / cm 2 ", other conditions remain unchanged; under the above conditions, the cycle performance of the aqueous zinc ion battery is tested. The results show that after 78h of cycling, the overpotential of the CR 2032 Zn / Zn pair battery tested under the condition of applying pulse current increases sharply to 0.117V, and the aqueous zinc ion battery is damaged.
[0069] Field emission scanning electron microscopy was used to observe the surface morphology of the negative electrode after the cycle. The test results showed that Zn had obvious large clusters of zinc deposition morphology on the negative electrode side, and dendrites occurred at the negative electrode during the cycle of aqueous zinc-ion batteries.
[0070] The above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for improving the cycle performance of an aqueous zinc ion battery, characterized in that: The method comprises applying a pulse current to an unoperated aqueous zinc ion battery; The aqueous zinc ion battery is powered on and off once as one cycle, and a plurality of cycles are repeated to form a pulse current; in each cycle, the power-on time is 1 to 10 seconds, the power-off time is 0.5 to 50 seconds, and the power-on-power-off time ratio is 1:0.5 to 1:5; the current density of the pulse current is 0.5 to 3 mA / cm 2 The power-on-power-off cycle is repeated until the negative electrode deposition capacity of the aqueous zinc ion battery is 0.5-3 mAh / cm 2 ; The electrolyte of the aqueous zinc ion battery is a zinc sulfate aqueous solution, a zinc tetrafluoroborate aqueous solution or a zinc trifluoromethanesulfonate aqueous solution; in the electrolyte, the concentration of zinc ions is 0.2-5 mol / L.
2. A method for improving the cycle performance of an aqueous zinc ion battery according to claim 1, characterized in that: In each cycle, the power-on time is 1 to 10 seconds and the power-off time is 3 to 50 seconds; the power-on-power-off cycle is repeated until the overpotential of the aqueous zinc ion battery reaches above 0.1V.
3. A method for improving the cycle performance of an aqueous zinc ion battery according to claim 1, characterized in that: The positive electrode and the negative electrode of the aqueous zinc ion battery are respectively independent zinc foils or zinc alloy foils.
4. A method for improving the cycle performance of an aqueous zinc ion battery according to claim 1, characterized in that: The diaphragm of the aqueous zinc ion battery is a glass fiber membrane, a polypropylene membrane or a polyethylene membrane.
5. A method for improving the cycle performance of an aqueous zinc ion battery according to any one of claims 1 to 4, characterized in that: The positive electrode and negative electrode materials of the aqueous zinc ion battery are respectively independent zinc foils; the diaphragm of the aqueous zinc ion battery is a glass fiber membrane; the electrolyte of the aqueous zinc ion battery is a zinc sulfate aqueous solution, and the concentration of zinc ions in the electrolyte is 2 mol / L.
Citation Information
Patent Citations
Process of charging an electrochemical generator having zinc negative electrodes and an electrochemical generator for putting the process into practice
US4730153A